Fano Resonance Properties in (K3C6o / HgBa2Ca2Cu3O10) 1D photonic crystal. Issue 1 (October 2020) - Aly, Arafa H; Mohamed, D.; Abd El-Gawaad, N. S.; Matar, Z. S.; Trabeisi, Y.; Mohaseb, M. A.
Abstract: The Fano resonance and Electromagnetic induced reflectance (EIR) properties in one-dimensional superconductor photonic crystals (SPCs) have been investigated theoretically by Transfer Matrix Method (TMM). The periodic structure consists of alternating of pair superconductor materials are made of (K3 C60 /HgBa2 Ca2 Cu3 O10 ) one-dimensional photonic crystal. The SPCs is enclosed by dielectric cap layer at different induced fields. To exam the efficiency of the reported structure, different parameters are used for analysis such as layers thicknesses, temperature, angle of incidence and the dielectric constant, dielectric cap layer on the EIR and Fano line shape. The investigation results exhibits tunable Fano resonances and EIR resonance peaks accompanied by asymmetrical line shape very sensitive to dielectric cap layer, constituent materials and dependence incidence angle. This will be useful reference for different applications of photonic topological states in the integrated photonic devices and information processing chips.